A New Method of Multiple Plane Curve Numerical Synthesis - Zhang Zhizi; Tang Jinyuan (Jixie chuandong)
Aiming at the problem of numerical synthesis on conjugate curve processed by pre-grinding bob,a new method of arbitrarily complex multiple plane curves numerical synthesis to a curve is given. In this method,the curve is dispersed into points and establishing a matrix,after amplification,the discrete data point is put in the matrix to compare the size,and achieve synthesis. Applying this method,the synthesis validation is carried out through the tooth root conjugate curve processed by C type pre-grinding hob.